Lysimachia xiangxiensis (Primulaceae), a new species from limestone area in Hunan Province, central China - Mou, Cun (PhytoKeys, 2020)
Abstract. A new species of Lysimachia, L. xiangxiensis (Primulaceae), is described and illustrated from western Hunan, central China. The species is similar to L. melampyroides in plant densely strigillose, leaves subglabrous adaxially, and flowers usually solitary in axils of upper leaves, but differs by the succulent leaves, the creeping or ascending stems 15–25 cm long, and the suborbicular to broadly elliptic corolla lobes. This new species is also supported by a molecular phylogenetic analysis of some Lysimachia species based on ITS sequence data.